Educational intervention about palliative care aimed at people with malignant cutaneous tumor wounds: Nurses' experience (Research, Society and Development, 2020)
Objective: to analyze the experience of nurses after participating in an educational intervention about palliative care aimed at people with malignant cutaneous tumor wounds. Method: This is an exploratory research, with a qualitative approach, carried out with 11 nurses who worked in the High Complexity Health Care in Oncology of Paraíba between the months of June and July 2018 and analyzed using the Bardin content analysis technique. Results: From the analysis, two categories emerged: Category 1 - There is always something to learn: deconstructing, reconstructing and transforming knowledge, which was divided into three subcategories and Category 2 - Redefining know-how: transforming care. Conclusions: It was found that the process of significant learning was the guiding thread for a reflective practice, since they re-signified knowledge and practices related to palliative care and transformed nursing care aimed at people with malignant cutaneous tumor wounds.